Does early extubation after cardiac surgery lead to a reduction in intensive care unit length of stay?. (10th February 2022) - Taylor, Marcus; Apparau, Denish; Mosca, Roberto; Nwaejike, Nnamdi
Summary: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was whether early extubation (EE) after cardiac surgery leads to a reduction in intensive care unit (ICU) length of stay (LOS)? A total of 564 papers were found using the reported search, of which 4 were randomized trials and hence represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. EE was defined as extubation in theatre ( n = 2), within 6 h of surgery ( n = 1) and within 8 h of surgery ( n = 1). EE was associated with significantly reduced ICU LOS in all studies. Despite the Society of Thoracic Surgeons using extubation <6 h after surgery as a measure of quality, this study has demonstrated that no standardized definition for EE currently exists. The body of evidence identified in this work has demonstrated that for appropriately selected patients (avoiding patients with multiple comorbidities, advanced age and undergoing complex non-elective surgery) early tracheal extubation is associated with a reduction in ICU LOS without an increase in the rate of postoperative complications. Abstract : A best evidence topic was constructed according to a structured protocol.